Analisis Pengaruh Rasio Likuiditas, Rasio Leverage, Rasio Profitabilitas Dan Kepemilikan Manajerial Terhadap Kebijakan Dividen - Edi Wijayanto; Anggi Navulani Putri (Politeknik Negeri Semarang, 2018)
Dividend policy is the decision taken by a company. Whether the dividends earned will be withheld or distributed in cash to investors. The dividend payout ratio determines the amount of profit divided into cash dividends and retained earnings as a source of funding. In this research focus on Dividend Policy (Dividend Payout Ratio). This study aims to determine the factors that can affect the dividend policy on the company. LQ-45 index in Indonesia Stock Exchange period 2011-2015. The sample used in this research are 8 companies by using purposive sampling technique. Data analysis technique used is panel data regression analysis operated by software eview8. Adjusted R2 value is 0,3736, it means that change of independent variable that is liquidity ratio (CR), leverage ratio (DER), profitability ratio (ROA) and managerial ownership can give contribution equal to 37,36% to change of dependent variable that is dividend policy (DPR) While the rest is explained by other variables. F test results show that the liquidity ratio (CR), leverage ratio (DER), profitability ratio (ROA) and managerial ownership simultaneously significantly influence dividend policy. While the result of t test show that leverage ratio variable (DER) and profitability ratio (ROA) partially have significant effect to dividend policy, variable of liquidity ratio (CR) and managerial ownership have no significant effect to dividend policy.